Analysis of morphing, multi-stable structures actuated by piezoelectric patches - Pedro Portela (2008)
In this article a novel morphing structure concept is studied using non-linear Finite Element Analysis (FEA). Bi-stable asymmetrical laminates can be snapped between two geometries through a buckling mechanism that is activated by an applied load. A piezoelectric Macro Fibre Composite (MFC) actuator was chosen to provide this activation load. Bi-stable structures will maintain a given geometrical state without the need for a constant actuation force. FEA was used to predict the two stable geometries, to understand the buckling mechanism and to evaluate the feasibility of using MFC actuators for switching between states. Environmental effects like moisture absorption were also included in the analysis.